Lysinibacillus fusiformis: a novel fibrolytic native strain from the rumen microbiome that increases in vitro digestibility of central agricultural residues - Marcela Guadalupe Téllez Martínez; José Luis; Navarrete Bolaños (Journal of Applied Animal Research, 2023)
Increasing the digestibility of agricultural residues is one goal of sustainable livestock production, and the role of rumen microbiome-feed interaction is critical for efficient digestion. This study was aimed at isolating and evaluating in vitro the effect on dry-matter digestibility (IVDMD), relative feed values (RFV), volatile fatty acid (VFA) synthesis, pH changes, and gas production (GP) by the inclusion of native rumen strains in mixtures of corn, sorghum, and oat agricultural residues with ruminal fluid. The results show that an inoculum of 1 × 1010 colony-forming unit per millilitre (CFU/mL) of the aero-tolerant native rumen strain Lysinibacillus fusiformis increases the IVDMD, RFV, and VFA values of all mixtures. During agricultural residue fermentation, the pH was stable, and propionic acid was the primary fatty acid synthesized, indicating increased energy availability for efficient cattle growth performance while limiting molecular hydrogen (H2) synthesis for conversion to methane (CH4). These results suggest that L. fusiformis could be used as a direct-feed microbial to promote sustainable livestock production. To the best of our knowledge, this is the first report to link the fermentation of fibrous agricultural residues in ruminal fluid inoculated with a fibrolytic native strain and digestibility in favour of increasing the efficiency of livestock production.